2000
DOI: 10.1038/35012001
|View full text |Cite
|
Sign up to set email alerts
|

Detection of weak gravitational lensing distortions of distant galaxies by cosmic dark matter at large scales

Abstract: Most of the matter in the Universe is not luminous, and can be observed only through its gravitational influence on the appearance of luminous matter. Weak gravitational lensing is a technique that uses the distortions of the images of distant galaxies as a tracer of dark matter: such distortions are induced as the light passes through large-scale distributions of dark matter in the foreground. The patterns of the induced distortions reflect the density of mass along the line of sight and its distribution, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
538
2
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 559 publications
(550 citation statements)
references
References 33 publications
7
538
2
3
Order By: Relevance
“…Mould et al (1994) searched for cosmic shear and reached percent-level sensitivity, but did not detect a signal. Cosmic shear was finally detected in 2000 by several groups (Wittman et al, 2000;Bacon et al, 2000;Van Waerbeke et al, 2000), and in deeper but narrower data from HST (Rhodes et al, 2001;Refregier et al, 2002). Over the same period, several additional square degrees were observed with long exposure times in excellent seeing using ground-based telescopes (Van Waerbeke et al, 2001Bacon et al, 2003;Hamana et al, 2003).…”
Section: Cosmic Shearmentioning
confidence: 95%
“…Mould et al (1994) searched for cosmic shear and reached percent-level sensitivity, but did not detect a signal. Cosmic shear was finally detected in 2000 by several groups (Wittman et al, 2000;Bacon et al, 2000;Van Waerbeke et al, 2000), and in deeper but narrower data from HST (Rhodes et al, 2001;Refregier et al, 2002). Over the same period, several additional square degrees were observed with long exposure times in excellent seeing using ground-based telescopes (Van Waerbeke et al, 2001Bacon et al, 2003;Hamana et al, 2003).…”
Section: Cosmic Shearmentioning
confidence: 95%
“…The first detections of cosmic shear on wide-field imaging data (Bacon et al 2000(Bacon et al , 2002Kaiser et al 2000;van Waerbeke et al 2000van Waerbeke et al , 2001van Waerbeke et al , 2002Wittman et al 2000;Maoli et al 2001;Rhodes et al 2001;Hämmerle et al 2002;Hoekstra et al 2002;Refregier et al 2002) has demonstrated the feasibility of this new window of observational cosmology, and yielded already the first constraints on cosmological parameters, most noticibly the normalization σ 8 of the dark matter power spectrum, but also on the matter density parameter Ω m Hoekstra et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Gravitational lensing of the cosmic microwave background (CMB), for instance, was first detected (Smith et al 2007) by cross-correlating noisy CMB lensing maps with a catalog of radio galaxies. Similarly, in the context of galaxy lensing, the cross-correlation of lensing induced shearing of background galaxies with the positions of foreground galaxies (known as galaxy-galaxy lensing) was detected (Brainerd et al 1996) before shearshear correlations (Bacon et al 2000;Kaiser et al 2000;Van Waerbeke et al 2000;Wittman et al 2000). Furthermore, lensing-tracer cross-correlation measurements are typically less sensitive to additive systematic errors since these will tend to average to zero in the cross-correlation (assuming the sources of systematic error are uncorrelated between the lensing measurements and the tracer measurements, often a reasonable approximation).…”
mentioning
confidence: 98%